Relating to Place as Property with Merton as Guide - Oyer, Gordon (The Merton annual, 2025)
The concept of private property anchors much of modern Western life, yet we rarely question its origins or the validity of how we individually and collectively apply it. In tracing the concept's emergence and then asking how Thomas Merton perceived owning and economically utilizing our landscapes, this essay suggests ways his perspectives might guide our engagement with private property. It discusses Merton's recognition of limits upon and relational obligations inherent within private-property ownership, along with special challenges in how Americans in particular relate property ownership to their national identity and presumptions of freedom.